Lymphangioma circumscriptum - rare site - Kar, S; Mohankar, A; Krishnan, A (Health Renaissance, 2012)
22 year old male came to Skin department with grouped vesicles over sternal region since birth along with serous discharge. The biopsy taken from site showed histopathologically Lymphangioma circumscriptum. It was treated with CO2 Laser, and response was good. Health Renaissance; September-December 2012; Vol 10 (No.3);256-257 DOI: http://dx.doi.org/10.3126/hren.v10i3.7059